PERAN NILAI EMOSIONAL DALAM MEMEDIASI PENGARUH PERSEPSI KUALITAS TERHADAP NIAT BELI - Bimartha, Putu Angga Agusta; Aksari, Ni Made Asti (E-Jurnal Manajemen; Vol 8 No 4 (2019)DO - 10.24843/EJMUNUD.2019.v08.i04.p01, 2019)
This study aims to explain the influence of perceived quality and emotional value towards purchase intention of Nike Running Shoes, and the role of emotional value in mediating the influence of perceived quality on the purchase intention of Nike Running Shoes. This research was conducted on people living in Denpasar City. The population of this study is infinite. The number of samples used was 100 respondents and, was determined using non-probability sampling method with purposive sampling technique. The data was collected through survey using questionnaires and analyzed using path analysis techniques. The results show that quality perception have a positive and significant effect on emotional value, and perceived quality also have a positive and significant effect on purchase intention, while emotional value has a positive and significant influence on purchase intention and is able to mediate the relationship of perceived quality indirectly to purchase intention.